Community Service in the Higher Education Environment - Dede Ismawan; Nur Hidayat Tullah; Masduki Asbari; Dany Achmad Fauzan (CV. AGUSPATI RESEARCH INSTITUTA, 2022)
Community service is the implementation or application of science, technology, and cultural arts which is carried out directly to the community institutionally through scientific methodology as the dissemination of the Tri Dharma of Higher Education and has a high responsibility in developing community capabilities. The purpose of carrying out this research is to determine the implementation of policies and the implementation of research and community service programs in each university. The research method applies quantitative and qualitative methods with descriptive techniques. The research sample is a student of STMIK Insan Pembangunan who was selected purposively. Data collection tools and techniques are guidelines for documentation studies, interviews, and focus group discussions. Primary data is taken from speakers in universities, while secondary data is a document regarding laws and regulations and previously related research.